Lattice and magnetic dynamics of a quasi-one-dimensional chain antiferromagnet PbFeBO4. (14th November 2016) - Prosnikov, M A; Smirnov, A N; Yu Davydov, V; Sablina, K A; Pisarev, R V
Abstract: A group of recently synthesized orthorhombic Pnma crystals Pb M BO4 ( M   =  Cr, Mn, Fe) demonstrates a number of unusual structural and magnetic properties. We report on polarized Raman scattering study of the lattice and magnetic dynamics in single crystals of an antiferromagnet PbFeBO4 below and above T N = 114 K. Polarization properties of the observed magnetic excitations below T N as well as intense quasi-elastic scattering support the quasi-one-dimensional character of the magnetic structure of PbFeBO4 . Frequency overlapping of magnetic excitations and low-frequency phonons in the range of 90–200 cm −1 leads to pronounced asymmetric anomalies thus confirming intrinsic coupling of magnetic and lattice subsystems. This conclusion is also supported by observation of anomalous temperature behaviour of higher frequency phonons in the vicinity of T N . Experimental investigations are supported by relevant magnetic symmetry analysis which allows us to explain previously observed anomalous results.